السياسة الجنائية في جرائم الاخلاق - هاشم محمد احمد الجحيشي (PROSPECTIVE RESEARCHES, 2023)
Criminal Policy is a collection of items and sources that help determine the legislator in his process of criminalizing and punshing some behaviours. At the same time, it urges the legistor to avoide much of these behaviours within criminal punishment, or incorporating her discarding them when factors of permission are available. The same applies for behaviours of moral erimes where the philosophy on which the positivist criminal policy is based adopts the social utilitarian sense that permits the freedom of consensuat sexual intercourse when most practiced in public. However, this does not apply when either party or both of them are subject to a valid legal marriage contract. Meanwhile, the criminal philosophy adopted by Islamic sharica in confronting moral crimes is based on moral significance which aims at safeguarding issues of honour and maintaining public morals. This significance considers any sexual contact out of wedlock contract a real crime regardless of the views of parties to it or the attitude of prevailing customs and conventions of public opinion.